2018
DOI: 10.5056/jnm16167
|View full text |Cite
|
Sign up to set email alerts
|

Bifidobacterium longum and Lactobacillus helveticus Synergistically Suppress Stress-related Visceral Hypersensitivity Through Hypothalamic-Pituitary-Adrenal Axis Modulation

Abstract: Background/AimsVisceral pain and hypothalamic-pituitary-adrenal axis (HPA) dysregulation is a common characteristic in irritable bowel syndrome (IBS) patients. Previously, we reported that a probiotic formulation (Lactobacillus helveticus R0052 and Bifidobacterium longum R0175) prevents chronic stress-mediated brain function abnormalities by attenuating the HPA axis response. Here, we compared the effect between different probiotic treatments on the perception of visceral pain during colorectal distension (CRD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
73
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 99 publications
(77 citation statements)
references
References 54 publications
(54 reference statements)
3
73
0
1
Order By: Relevance
“…HES1 is responsible for maintaining gut homeostasis via preventing microbial dysbiosis in the mouse, and HES1‐knockout altered colon crypt morphology . The probiotic combination of Lactobacillus helveticus and Bifidobacterium longum helped reverse WA‐stress‐induced changes in the mouse hypothalamic‐pituitary‐adrenal axis and WA stress‐induced visceral hyperalgesia by blocking decrease of NR3C1 in the hypothalamus, hippocampus and prefrontal cortex . These reports support the potential of HES1‐CLDN1 and NR3C1 acting as equilibrium maintaining gene circuits consists of three genes that regulate each other in a cyclical manner and their potential roles in homeostasis of the Microbiota‐Gut‐Brain Axis.…”
Section: Some Potential Applications Of Turing Pattern Analysis In Gamentioning
confidence: 75%
See 3 more Smart Citations
“…HES1 is responsible for maintaining gut homeostasis via preventing microbial dysbiosis in the mouse, and HES1‐knockout altered colon crypt morphology . The probiotic combination of Lactobacillus helveticus and Bifidobacterium longum helped reverse WA‐stress‐induced changes in the mouse hypothalamic‐pituitary‐adrenal axis and WA stress‐induced visceral hyperalgesia by blocking decrease of NR3C1 in the hypothalamus, hippocampus and prefrontal cortex . These reports support the potential of HES1‐CLDN1 and NR3C1 acting as equilibrium maintaining gene circuits consists of three genes that regulate each other in a cyclical manner and their potential roles in homeostasis of the Microbiota‐Gut‐Brain Axis.…”
Section: Some Potential Applications Of Turing Pattern Analysis In Gamentioning
confidence: 75%
“…These reports support the potential of HES1‐CLDN1 and NR3C1 acting as equilibrium maintaining gene circuits consists of three genes that regulate each other in a cyclical manner and their potential roles in homeostasis of the Microbiota‐Gut‐Brain Axis. Future advances in personalized probiotics based, in part, on 4D Nucleome algorithms represent a potentially promising therapeutic area …”
Section: Some Potential Applications Of Turing Pattern Analysis In Gamentioning
confidence: 99%
See 2 more Smart Citations
“…Authors found that one month intake of fermented milk product with probiotic in healthy women was associated with alteration in activity of brain regions that control central processing of emotion and sensation. In this issue of the Journal of Neurogastroenterology and Motility, 16 authors from France, Canada, Sweden studied the comparative effects of treatment of mice with different probiotics (B. longum and L. helveticus) for 2 weeks on the perception of visceral pain induced by colorectal distension after chronic stress and on the activity of the HPA axis. The authors concluded that the combination of the 2 probiotics showed greater efficacy than either alone in regulating glucocorticoid induced negative feedback on the HPA axis; hence, they suggested that this observation may have implication in the treatment of stress-induced visceral pain.…”
mentioning
confidence: 99%